The talisman of happiness : 1,680 recipes : the most iconic Italian cookbook ever written - Boni, Ada (Voracious, 2025)
In 1929, two years before The Joy of Cooking was published in America, and two decades before The Silver Spoon in Italy, Ada Boni wrote The Talisman of Happiness--the original must-have culinary bible for Italians. Generations of cooks have turned to "Il Talismano" as the definitive source for classic dishes that bring comfort, nostalgia, and deep pleasure--including the iconic Marcella Hazan, who used the book to teach herself how to cook.... In this landmark first English edition of the complete work, featuring nearly 1,700 recipes, American cooks can finally appreciate Talisman in full. Carefully translated to preserve the spirit and warmth of the original, this new edition makes the richness of Italy's regional cooking accessible to all--and includes American measurements, delightful illustrations, and forewords by Lidia Bastianich and Katie Parla.--Publisher description.